2021
DOI: 10.1111/ajt.16528
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow-derived mesenchymal stromal cell therapy with early tacrolimus withdrawal: The randomized prospective, single-center, open-label TRITON study

Abstract: This is an open access article under the terms of the Creative Commons Attribution NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 30 publications
3
48
0
Order By: Relevance
“…A number of clinical trials have been designed to evaluate the safety and efficacy of MSC-based therapy and some good results have been observed in acute kidney injury trials ( 179 ). Very recently, the TRITON study ( 180 ) has used the infusion of autologous MSCs in 29 kidney transplant recipients to withdraw CNI. After 24 weeks of follow up, no differences were observed in graft function, acute rejection, graft loss, major adverse events or in kidney fibrosis.…”
Section: The Reparation Mechanismsmentioning
confidence: 99%
“…A number of clinical trials have been designed to evaluate the safety and efficacy of MSC-based therapy and some good results have been observed in acute kidney injury trials ( 179 ). Very recently, the TRITON study ( 180 ) has used the infusion of autologous MSCs in 29 kidney transplant recipients to withdraw CNI. After 24 weeks of follow up, no differences were observed in graft function, acute rejection, graft loss, major adverse events or in kidney fibrosis.…”
Section: The Reparation Mechanismsmentioning
confidence: 99%
“…On the other hand, Tan et al reported that MSC administration enabled lower dose of calcineurin inhibitor (CNI) immunosuppressants, without compromising graft function or acute rejection occurrence [ 21 ]. Reinders et al recently demonstrated that MSCs infused at 6 and 7 weeks after kidney transplantation allowed the withdrawal of tacrolimus without deterioration in graft function or increase in rejection rates [ 22 ]. Although these data provided a great promise for the application of MSCs as cellular therapeutics to improve the allotransplantation outcomes, discrepancies between studies imply the scope for optimization, which can be considered in the process of MSC preparation and administration.…”
Section: Mscs In Allotransplantation and Limitationsmentioning
confidence: 99%
“…Cell therapy in organ transplantation is an emerging field. Recent clinical trials have mainly focused on the early stage of transplantation, in order to decrease the burden of immunosuppressive agents or induce organ tolerance [10][11][12][13]. Mesenchymal stromal cells (MSCs) are currently the most evaluated cell type and the closest to being used in routine clinical practice.…”
Section: Mesenchymal Stromal Cells To Slow Down Fibrosismentioning
confidence: 99%
“…The two subsequent recipients were infused with MSCs before KTx (2.0 9 10 6 cells/kg), without any consequent inflammatory infiltrates in the kidney graft [15]. Two recent trials, the TRITON study [13] and the NEP-TUNE study [16] tested another approach, i.e. a delayed infusion of MSCs after several weeks post-KTx.…”
Section: Mesenchymal Stromal Cells To Slow Down Fibrosismentioning
confidence: 99%